Exploratory Study of Factors Influencing Employee Engagement in Medium-Scale Manufacturing Companies in Semarang Regency - Krisdayanti Telaumbanua; Dyah Palupiningtyas (International Journal of Economics and Management Research, 2025)
This research aims to explore factors influencing employee engagement in medium-scale manufacturing companies in Semarang Regency. Using a qualitative approach with in-depth interviews and focus group discussions, the study involved 67 employees from five manufacturing companies. The results identified six main factors influencing employee engagement: leadership, work environment, career development, compensation, organizational culture, and communication. Transformational leadership emerged as the dominant factor, followed by physical and psychosocial work environment. The research found variations in factors based on demographic characteristics, where younger employees were more influenced by career development, while senior employees were more responsive to leadership and organizational culture. The study produced a conceptual model of employee engagement that considers interactions between factors and Indonesia's specific socio-cultural context. Practical implications include the importance of prioritizing leadership development and creating a conducive work environment to enhance employee engagement in companies with limited resources. This model provides a framework for developing effective and personalized HR management strategies in medium-scale manufacturing companies in Indonesia.